FACTORS INFLUENCING A BOND RATING ON A MANUFACTURING COMPANY - Mubarokah, Annisa Kharirotul; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The most important factor in managing a company is the company's financial resources. Companies can issue bonds as a form of financing. Investing in bonds is like lending money to issuers such as corporations or governments. When a company issues bonds, the funds increase business, such as working capital, debt repayment, expansion and other needs. The object of this study was production companies listed on the IDX in 2017-2019, which PT Pefindo classified. The ranking is carried out on the official website of PT Pefindo and the Indonesia Stock Exchange (IDX). The analysis results show that listeners do not affect warning ratings. This can be proven by the high-profit value of 0.884, which is greater than 0.05, and leverage does not affect bonding valuations which can be considered significant leverage. 0.257, which is greater than 0.05.